2009
DOI: 10.17221/1680-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Covariance components by a repeatability model in Slovenian dairy sheep using test-day records

Abstract: ABSTRACT:The estimation of covariance components for daily milk yield, fat and protein content was performed in three Slovenian dairy sheep breeds (Bovec, Improved Bovec, and Istrian Pramenka). In the period 1994-2002, 38 983 test-day records of 3 068 ewes were collected according to ICAR regulations (method A4). All the available relationships between animals were considered. For that reason, information on 3 534 animals was included. Test-day records were analysed by a multiple-trait repeatability animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Genetic evaluations of milk traits in dairy sheep are nowadays mainly performed by application of testday records (El-Saied et al, 1998a, Serrano et al, 2001, Oravcova et al, 2005, Komprej et al, 2009. Some advantages were found in such modelling of records (Ptak andSchaeffer, 1993, Serrano et al, 2001) in comparison to lactation yields (El-Saied et al, 1998a, El-Saied et al, 1998b, Portolano et al, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evaluations of milk traits in dairy sheep are nowadays mainly performed by application of testday records (El-Saied et al, 1998a, Serrano et al, 2001, Oravcova et al, 2005, Komprej et al, 2009. Some advantages were found in such modelling of records (Ptak andSchaeffer, 1993, Serrano et al, 2001) in comparison to lactation yields (El-Saied et al, 1998a, El-Saied et al, 1998b, Portolano et al, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Heritabilities for dairy traits on a total lactation basis are low to moderate for milk, fat, and protein yields (Komprej et al 2009;Bauer et al 2012;Dimov 2013) and high for fat and protein percentages (Pelmus et al 2014). Duchemin et al (2012) showed that utilization of molecular markers can improve current selection methods.…”
Section: Sheepmentioning
confidence: 99%
“…Relationships between the milk production and the fecundity traits (litter size, number of weaned lambs) should be further analyzed by including a multi-trait approach. The milk-component effects could be used to optimize BV for milk product yield, as the dry matter content and the milk yield are negatively correlated (Othmane et al, 2002;Komprej et al, 2009), and product yield depends on both the parameters. When more records are available and the data have better connectedness, which can be facilitated by broader production recording, the random regression of days-in-milk should be tested as well.…”
Section: Potential Models For a Further Developmentmentioning
confidence: 99%